Lose weight by eating : detox week : twice the weight loss in half the time with 130 recipes for a crave-worthy cleanse - Johns, Audrey (William Morrow, an imprint of HarperCollins Publishers, 2017)
The author of the popular blog by the same name draws on the experiences of her own weight-loss journey to outline customizable approaches to dieting, in a reference that is complemented by dozens of recipes for meals designed to accelerate weight loss by naturally raising the metabolism.